Applicability of Criminological Ideas in the Control of Juvenile Crime - Kolaković, Milica (Zbornik Instituta za kriminološka i sociološka istraživanja, 2008)
A few decades of looking for the best strategies in the struggle against juvenile crime resulted in many different concepts. The best distinction between those concepts are made using the answers to three questions: -Firstly, what are the major factors in the etiology of juvenile crime? -Secondly, which type of social reaction to juvenile offence is the most hopeful? -Thirdly, how should we treat juvenile criminals? We can find answers to those questions in the acceptance of some ideas from criminological theories. Considering that, we tried to focus on some ideas that can be useful but also dangerous, in light of the theories of interactionism, labelling and reintegrative shaming. Using those ideas in criminal legislation and practice could be an important influence on the control of the criminal.